First Principles Enhanced Electronic Band Structure of Back Contact in CdTe Solar Cells using DFT+U Method - Ahmad N.I.; Azizan N.; Kar Y.B.; Doroody C.; Arshad S.N.M.; Abdullah A.Z.; Jamal A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Cadmium telluride (CdTe) superstrate solar cells have captivated the industry with their remarkable cost-effectiveness. However, optimizing the composition and optoelectrical properties of optimal back surface field (BSF) which can act as a lattice matching interface between the back contact and absorber layer remains a key challenge due to the work function disparity of p-CdTe with metal contacts. In this study, the influence of the Hubbard U parameter on the calculated electronic properties of ZnTe as an optimal BSF compound is presented using the density functional theory (DFT) technique. The Hubbard U value progressively increased from 1 to 4.2 to analyze its influence on the band diagram and Total Density of States (TDOS) in a full comparison of DFT and DFT+U approaches. As the value of Hubbard U increased, the band gap energy exhibited a corresponding increase from 1.20 eV to 2.24 eV, respectively. In comparison, the DFT+U approach with a value of 4.2 exhibited superior accuracy in predicting the band gap of ZnTe, yielding a value of 2.24 eV that closely approximated experimental measurements. This finding reinforces the relevance of employing Hubbard U to achieve more accurate and reliable band gap values for any material doping. 2023 IEEE.